2013
DOI: 10.1080/1091367x.2013.831763
|View full text |Cite
|
Sign up to set email alerts
|

The Psychometric Properties of the Short and Long Versions of the Coach–Athlete Relationship Questionnaire

Abstract: The Coach-Athlete Relationship Questionnaire was developed to effectively measure affective, cognitive, and behavioral aspects, represented by the interpersonal constructs of closeness, commitment, and complementarity, of the quality of the relationship within the context of sport coaching. The current study sought to determine the internal reliability and factorial validity of the long (the 29-item Long Version Coach-Athlete Relationship Questionnaire) and short (11-item Coach-Athlete Relationship Questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 32 publications
4
14
0
Order By: Relevance
“…The CFA for the Coach-Athlete Relationship Questionnaire shows a good internal consistency [χ 2 (41) = 136.473; p < 0.001; RMSEA = 0.075, p < 0.001; CFI = 0.940; SRMR = 0.043]. Factor correlation is between 0.93 and 0.97, and this could indicate collinearity problems between factors: the literature reveals a high correlation among those dimensions, and many studies try to validate a single factor structure without obtaining satisfactory results ( Yang and Jowett, 2012 , 2013 ). For the Peer Motivational Climate in Youth Sport-Questionnaire, the CFA shows that only four factors over five resulted in being reliable in our sample; therefore, in the analysis, we only considered focus on improvement, effort, intrateam competitiveness, intrateam conflict.…”
Section: Resultsmentioning
confidence: 99%
“…The CFA for the Coach-Athlete Relationship Questionnaire shows a good internal consistency [χ 2 (41) = 136.473; p < 0.001; RMSEA = 0.075, p < 0.001; CFI = 0.940; SRMR = 0.043]. Factor correlation is between 0.93 and 0.97, and this could indicate collinearity problems between factors: the literature reveals a high correlation among those dimensions, and many studies try to validate a single factor structure without obtaining satisfactory results ( Yang and Jowett, 2012 , 2013 ). For the Peer Motivational Climate in Youth Sport-Questionnaire, the CFA shows that only four factors over five resulted in being reliable in our sample; therefore, in the analysis, we only considered focus on improvement, effort, intrateam competitiveness, intrateam conflict.…”
Section: Resultsmentioning
confidence: 99%
“…9,13 CART-Q's psychometric properties have been widely tested throughout the world, supporting the multidimensional nature of the instrument through its three distinct, yet connected, dimensions of closeness, commitment, and complementarity, addressing the emotional, cognitive, and behavioral elements of the 3 + 1Cs Model. 8 So far, the psychometric properties of this instrument were verified in Belgian coaches, 14,15 Iranian coaches, 16 Chinese coach and athletes, 17,18 Turkish coaches and athletes, 19 and Polish coaches. 20 Some of these studies have observed significant variations for the latent construct values between countries 15 and, therefore, indicate the need of performing all of the psychometric procedures with the goal of assessing how effective the questionnaire is, for the context that is intended to be studied.…”
Section: Introductionmentioning
confidence: 93%
“…In the last decade, coach-player relationships have been the subject of great interest among researchers (Yang & Jowett, 2013), as these relationships have interpersonal dynamics that influence the quality of players' and coaches' personal experiences, the degree of successful coaching, the performance success of the players, and the level of psychological well-being (Jowett & Cockerill, 2003;Lyle, 2002;Poczwardowski, Barott, & Jowett, 2006;Yang & Jowett, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this study is the first reliability and validity study of LMX. In addition, during the last decade, scholars have focused on measuring the quality of relationships between coaches and players (Yang & Jowett, 2013). However, their measurements were based on an investigation of common practices and group dynamics in team sports and coaching, and they have not clearly indicated the active role of players in terms of relationship quality in the coach-player relationship process (Breukelen et al, 2012).…”
mentioning
confidence: 99%